Empowering the Manimbahoi Village Community through Digital Marketing Training: Pemberdayaan Masyarakat Desa Manimbahoi melalui Pelatihan Digital Marketing - Ahmar, Ansari Saleh; Rais, Zulkifli; Bakri, Rizal; Asmar, Asmar (Yayasan Ahmar Cendekia Indonesia, 2024)
This training was held in the Manimbahoi Village Meeting Room, Parigi District, Gowa Regency, South Sulawesi Province on August 31, 2023. Participants in this training were young people from Karang Taruna, with the aim that the community, especially young people in Manimbahoi Village, could understand the importance of digital marketing as an effort to market Manimbahoi coffee products not only in the Parigi District area but also to the National area. This community service activity went smoothly and as expected. The results of this service show that there has been an increase in the abilities and knowledge of the village community from not knowing to knowing about digital marketing for coffee marketing. Abstrak Pelatihan ini dilaksanakan di Ruang Pertemuan Desa Manimbahoi, Kecamatan Parigi, Kabupaten Gowa, Provinsi Sulawesi Selatan pada tanggal 31 Agustus 2023. Peserta dari pelatihan ini adalah pemuda karang taruna, dengan tujuan warga masyarakat khususnya pemuda di Desa Manimbahoi dapat memahami tentang pentingnya digital marketing sebagai upaya untuk memasarkan produk kopi Manimbahoi bukan hanya di daerah Kecamatan Parigi tetapi bisa ke kawasan Nasional. Kegiatan pengabdian ini berjalan lancar dan sesuai dengan yang diharapkan. Hasil dari pengabdian ini, terlihat bahwa terjadi peningkatan kemampuan dan pengetahuan masyarakat desa dari tidak tahu menjadi tahu tentang digital marketing untuk pemasaran kopi.